Death row women: murder, justice, and the New York press - Gado, Mark (Crime, media, and popular culture, 2008)
Introduction -- Blonde fiends and giggling grandmas -- A morality play : Ruth Snyder -- Dead a thousand times : Anna Antonio -- Eva Coo and murder on Crumhorn Mountain -- Rough on rats : Mary Frances Creighton -- A nuisance to society : Helen Fowler -- Martha Beck, the lonely heart -- A difficult concept